Upaya Manajemen Hotel di Makassar dalam Mengurangi Sisa Makanan (Food Waste) - Nugraha, Putu Ari; Darmayasa, Darmayasa; Aini, Windra; Pastini, Ni Wayan (Politeknik Bosowa, 2025)
This research examines the management strategies of 3 and 4 star hotels in Makassar in reducing food waste, as well as the challenges faced in its implementation. Food waste in the hotel sector, especially in buffet services, is a complex problem and has an impact on the economy and the environment. This research uses a qualitative descriptive method, with data collected through interviews and observation. The research results show that hotels in Makassar have implemented various strategies to reduce food waste, such as educating guests and staff, verbal and written appeals, and managing leftover food that is still fit for consumption. However, guest resistance to this appeal as well as management's concerns about the hotel's image are significant obstacles. This article suggests that more systematic and innovative approaches be implemented to reduce food waste in a sustainable manner.